Impact of Financial Modelling of Concrete Waste Using Life Cycle Assessment and Damage Cost - Saeed , Mohamed; Yas, Harith (International Journal of Accounting and Economics Studies, 2025)
Over the last two decades, Dubai has seen remarkable infrastructural growth, resulting in a corresponding increase in concrete debris being ‎dumped in landfills around the United Arab Emirates (UAE). There is a serious environmental problem since the number of building and ‎demolition sites has increased faster than the availability of efficient waste management options. Putting this concrete debris in landfills is ‎dangerous for people, animals, and the environment. To solve this problem, researchers performed a thorough Life Cycle Assessment (LCA) ‎to effectively evaluate the environmental effects of landfilling against those of recycling concrete debris. The purpose of the analysis was to ‎determine the financial impacts of different waste management strategies. By ISO 14040:2006, a systematic LCA procedure was used to ‎conduct the research. We utilized the EcoInvent 3.4 database and the SimaPro 8.5.2.0 program to streamline the LCA steps and provide ‎clearer outcomes. Damage prices linked with different environmental consequences were also calculated using the Handbook of Environmental Prices 2017. Damage cost and Life Cycle Impact Assessment (LCIA) comparisons show that recycling is much more cost-effective ‎than landfilling. The former has been demonstrated to have much greater impacts on the environment than the latter, which involves recycling and transporting concrete debris. The importance of this research lies in its provision of LCA conclusions related to concrete waste ‎management solutions, including landfilling, recycling, transportation, and the advancement of modeling methodologies for calculating damage costs. It draws attention to the critical need for more environmentally friendly methods of waste management and provides helpful ‎insights into those methods' effects on the natural world. This study suggests identifying crucial impact indicators and management methods ‎with significant environmental impacts. In addition, a Life Cycle Cost Analysis (LCCA) might be performed to support the results by calculating the savings from using various concrete waste management techniques. In conclusion, Dubai has a significant difficulty with its ‎growing concrete waste problem due to the city's rapid infrastructure development. Life cycle assessments (LCAs) that compare landfilling ‎versus recycling emphasize the necessity of sustainable waste management. This research not only improves our knowledge of damage cost ‎modeling but also provides a thorough analysis of potential solutions for dealing with concrete waste, which can help guide policymakers ‎toward more effective responses‎.